Identifying hydrologic reference stations to understand changes in water resources across Vietnam - a data-driven approach - Do H., X.; Le -H., M.; Pham H., T.; Le H., T.; Nguyen B., Q. (Vietnam Journal of Earth Sciences, 2022)
Among the impacts of climate change and variabilities, change in the terrestrial water cycle has been investigated extensively due to the importance of water resources to the Earth System. The detection and attribution of changes in river flows, however, are usually complicated by the impacts of on-ground human activities such as urbanization or dam construction that have altered flow regimes. As a result, hydrological reference stations – gauges measuring river flows of catchments that are unregulated - have been identified in many countries to provide streamflow records that are suitable for climate studies. Such a network, to the best of our knowledge, has not been promoted widely in Vietnam, making it difficult to determine the actual impact of climate change and variability to river flow regimes at the national scale. To address this limitation, this study uses a data-driven approach to identify stations that have not been influenced substantially by human activities for Vietnam. Specifically, we have carefully assessed streamflow records at 68 locations that are not influenced by tidal regime to identify stations with relatively good data quality. The drainage area associated with each of these stations was then delineated following international standards, and then used to identify catchments that were not associated with large dams. The catchment boundary was also used to extract land surface information, available through an ensemble of different satellite-based data products, to further identify catchments that are not featured by large urban areas, or experienced a substantial change in land cover during the 2000-2019 period. Using these criteria, this study suggested two subsets of stations distributed across the countries, providing a good starting point for future investigations into the impacts of climate change on water resources in Vietnam. The investigation also suggests that more investments are required to maintain and expand the hydrologic reference network for Vietnam.